Design of a fast digital double relaxation oscillation SQUID. - Podt, M.
A fast digital Double Relaxation Oscillation SQUID (DROS) with a relaxation oscillation frequency of 100 MHz has been developed. The digital DROS incorporates a DROS and a superconducting up-down counter that supplies the feedback flux. The major advantage of a DROS is that the relaxation oscillations generate an on-chip clock signal and therefore, no external clock is required. In order to maximize the slew rate without compromising the sensitivity, the quantization unit of the feedback flux was adapted to the flux noise of the DROS. This resulted in a designed flux slew rate of 5·106 Φ0/s. We will discuss the design optimization, numerical simulations, the layout and some experimental results of the digital DROS
Keywords: Design optimization; Digital integrated circuit; Double relaxation oscillation SQUID; Feedback flux; Flux noise; Numerical simulation; On-chip clock signal; Quantization unit; Sensitivity; Slew rate; Smart DROS; Superconducting up-down counter